Investigating Abetting Jurisprudence And Its Implementation With Iran Thetical Law By Focusing On The New Ipc (Islamic Penal Code) Adopted In 1392 - Dahmardeh, Ehsan; Khammar, Mohammad Amin (The Turkish Online Journal of Design Art and Communication, 2016)
One of the major issues in the IPC is the problem of accomplice in the crime, which is considered less. However, it can be seen that, this has an important place in jurisprudential rules. It can be seen that with reset refine in accordance with denial of contributions in crime rule, from the perspective of Islamic scholars, both Shia and Sunnite In terms of crime and sin and does not leave any doubt to investigators and lawyers and the general public, So that studies show, extending of the jurisprudential rule will spread In all dignities of people social life. But The Islamic Penal Code has the ambiguities related to accomplice in the crime, so, in the new IPC (Islamic Penal Code) adopted in 1392 was subject to review by the legislator. Accordingly, this study Investigated abetting jurisprudence and its implementation with Iran thetical law by focusing on the new IPC (Islamic Penal Code) adopted in 1392. The results showed these changes are due to the fact that in some cases, abrogating some of the provisions of previous legislation but the reforms have brought good results and has not in contradiction with jurisprudential rules.
Keywords: The Islamic Penal Code; accomplice in the crime; contributions on of sin; jurisprudential rule